2016
DOI: 10.1111/fwb.12864
|View full text |Cite
|
Sign up to set email alerts
|

Water abstraction impacts stream ecosystem functioning via wetted‐channel contraction

Abstract: Summary Water abstraction is rapidly increasing worldwide in order to respond to escalating demands for water, food and energy. Abstraction can alter the hydrological regime of streams and rivers, reduce in‐stream habitats, change water quality and affect fluvial communities. It can also impair ecosystem functioning, although this aspect has been seldom assessed. We experimentally tested the effect of water abstraction on stream functioning in a headwater mountain stream using a before and after control‐impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 109 publications
0
26
0
1
Order By: Relevance
“…Whatever the reason, the results show that the Pyrenean desman positively selects riffles rather than runs or pools, and more so in rivers affected by water diversion. Water diversion reduces the wetted channel (Stanley, Fisher, & Grimm, ), alters hydraulics (McIntosh et al, ), reduces the populations of benthic invertebrates (James, Dewson, & Death, ), and exerts impacts on stream ecosystem functioning (Arroita et al, ). The results suggest that water diversion can also have detrimental effects on the habitat of the endangered Pyrenean desman by reducing the availability of its preferred microhabitat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the reason, the results show that the Pyrenean desman positively selects riffles rather than runs or pools, and more so in rivers affected by water diversion. Water diversion reduces the wetted channel (Stanley, Fisher, & Grimm, ), alters hydraulics (McIntosh et al, ), reduces the populations of benthic invertebrates (James, Dewson, & Death, ), and exerts impacts on stream ecosystem functioning (Arroita et al, ). The results suggest that water diversion can also have detrimental effects on the habitat of the endangered Pyrenean desman by reducing the availability of its preferred microhabitat.…”
Section: Discussionmentioning
confidence: 99%
“…a threshold of discharge diverted beyond which habitat availability falls rapidly. Arroita et al (), using experimental flow manipulation in a stream similar to the Elama, demonstrated that environmental flows, as currently defined in the Basque Country, still severely reduce flow velocity and riffle abundance, thus strongly affecting stream ecosystem functioning. Therefore, it is likely that the very abundant diversion schemes in headwater streams in the Basque Country (Ente Vasco de la Energía (EVE), ), and elsewhere, are severely affecting desman habitat quality.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, there is a need to connect the fate of summer stream flow to land use practices (e.g., Price et al, ; Reed et al, ; Strauch et al, ; Sun et al, ; Weitzell et al, ), including water extraction (e.g., Arroita et al, ), as well as anticipated climate change (e.g., Asarian & Walker, ). In the Northern California Coast Ranges specifically, rapid expansion of cannabis cultivation is putting extreme pressure on summer water resources (e.g., Bauer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Drying events are likely to increase in frequency and duration in some regions of the globe as a result of climate change (Forzieri et al, 2014;Ledger & Milner, 2015;Pyne & Poff, 2017) and increasing pressure on water resources (Arroita et al, 2017). This study highlights the effect of surface water loss and increasing dry period duration on the survivorship of the common benthic macroinvertebrate G. pulex within saturated subsurface sediments.…”
Section: Discussionmentioning
confidence: 74%
“…These streams comprise a large proportion of the total channel length across the globe, occurring throughout climatic zones from the poles to the equator (Leigh et al, 2016a), making a significant contribution to regional biodiversity , but have typically been overlooked and excluded from national and international legislation protecting streams from anthropogenic degradation (Acuña et al, 2014(Acuña et al, , 2017. In some instances, historically perennial streams now experience intermittent flow and channel drying due to anthropogenic activities such as water abstraction, which captures some or all of the surface flow (Mackay et al, 2014;Arroita et al, 2017). The frequency and duration of 'no-flow' and streambed drying events may increase in some global regions based on future climate change predictions (Bonada et al, 2007a;Verdonschot et al, 2010;Ledger & Milner, 2015;Pyne & Poff, 2017), therefore, a greater understanding of the response of lotic ecosystems to drying duration would help guide future management options.…”
Section: Introductionmentioning
confidence: 99%